Spade Ethnomathematics: Developing Student Worksheets Through Egrang Batok Kelapa Games to Enhance Length Measurement Understanding in Second Grade - Musdhalifah, Syifa Hajina; Mufliva, Rosiana; Febianti, Darin Kamiliya; Ramadhani, Dea Nurlinda; Namira, Hilwa Shahnun; Al-Hamed, Naftaly Rahmy Nurrahmaniya; Fauzia, Faza Fuzna (International Conference on Elementary Education, 2025)
Elementary mathematics education frequently prioritizes procedural memorization, often neglecting to forge meaningful connections between mathematical concepts and students' everyday realities. This pedagogical approach frequently culminates in diminished conceptual understanding among learners. Such shortcomings are conspicuously apparent in the domain of length measurement, a topic that inherently demands hands-on, experiential learning opportunities to foster genuine comprehension. Scholarly literature underscores that weaving local cultural elements into mathematics instruction markedly bolsters student engagement and deepens their grasp of abstract ideas. The Egrang Batok Kelapa game, embodying a pertinent facet of indigenous wisdom, offers an authentic framework for imparting length measurement principles through non-standard units, such as footsteps, thereby bridging classroom theory with cultural relevance. This investigation devised an ethnomathematics-infused Student Worksheet employing the SPADE model—encompassing Singing, Playing, Analyzing, Discussing, and Evaluating—while integrating the Egrang Batok Kelapa game as a contextual learning tool. The primary aim was to elevate second-grade students' proficiency in comprehending non-standard length measurement via immersive, enjoyable, and culturally embedded activities. Adopting a Design and Development methodology aligned with the ADDIE model, the study utilized expert validation sheets and restricted trial assessments with students as key instruments. Outcomes revealed robust validity, with an 88.3% endorsement from subject matter and media specialists, alongside exceptional feasibility evidenced by a 93.3% approval in student trials. Ultimately, the SPADE model ethnomathematics-based worksheet demonstrated efficacy in augmenting elementary students' mastery of non-standard length measurement concepts, promoting a more holistic and culturally attuned educational experience.